MODERN TECHNOLOGIES FOR INCREASING THE REPRODUCTION LEVEL IN DAIRY CATTLE - Lyashenko V.V.; Balakirev N.A.; Yuldashbayev Yu.A.; Kayeshova I.V.; Karynbayev A.K.; Gubina A.V.; Prokhorov I.P. (Scientific Journal of Pedagogy and Economics, 2020)
. The work aims to study the features of herd reproduction in the conditions of a modern specialized unit for growing repair young animals. The studies were carried out in the conditions of Megaferma OOO in the Kuznetsky region, which is part of the Rusmolco Company in the Penza region, on the number of animals in the modern herd reproduction center. The object of the research was the replacement heifers of the Holstein breed; the subject of the research was: live weight of heifers in different technological periods and the efficiency of insemination of heifers with sexed and ordinary sperm. The studies show the dynamics of live weight of the Holstein heifers of different origin (Holland, the USA, Russia) during directed growing; the achievement of live weight of 350 kg was established by the period of the first insemination at the age 12 months; the Dutch heifers had a higher growth rate during all growing periods. The results of studies indicate that when using sexed semen, the pregnancy rate of heifers from the first insemination was 54.5%; 82.5% of heifers were received from the studied livestock, which is 29.5% more than from the insemination with ordinary semen. When inseminating with sexed semen of heifers of different origins (Hungary, Germany, Russia), the existing differences in the experimental groups were found. The pregnancy rate from the first insemination in the studied livestock ranged from 48.7 to 59.7%, and the yield of heifers - from 77.5 to 89.4%. Such indicators are consistent with the international practice of using sexed semen and with the guarantees of the semen producer. Consequently, an increase in the number of heifers in offspring allows breeding farms to abandon the acquisi-tion of expensive breeding young stock.